Pengaruh Hedonic Shopping Motivation Dan Utilitarian Value Terhadap Impulse Buying Dengan Shopping Lifestyle Sebagai Variabel Mediasi Pada Pembeli Di Sardo Swalayan - Dwi Alfi Rahmi; N. Rachma; M. Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT This research was conducted to determine the effect of Hedonic Shopping Motivation and Utilitarian Value on Impulse Buying with Shopping Lifestyle as a mediating variable for buyers in Sardo Swalayan. The location for conducting this research is located at Jalan Gajayana No.500, Dinoyo, Lowokwaru District, Malang City, East Java. 6514, in this study using explanatory research method which aims to explain the position of each variable and its effect between one variable with other variables, and the source of the data used is primary data by distributing linkert scale questionnaires to buyers at Sardo Swalayan. The sample calculation in this study uses the Slovin formula which produces 99 respondents. The results of this study are the variable hedonic shopping motivation and utilitarian value directly influence shopping lifestyle, next hedonic shopping motivation and utilitarian value directly affect impulse buying, and shopping lifestyle directly affect impulse buying, and hedonic shopping lifestyle and utilitarian value have an indirect effect on impulse buying through shopping lifestyle as a mediating variable Keyword: Hedonic shopping  motivation, utilitarian value, impulse buying, shopping lifestyle.